#Opinion count - 1st Public debate : Sexual harassment - Strathmore University (Strathmore University, 2018)
The sexual harassment debacle in Hollywood that has reverberated in diverse arenas in the U.S and around the worlds, dubbed #MeToo has featured prominently in the media for now 3 months. Sexual harassment knows no position, choice, autonomy, gender or class, therefore we take it to Law in consideration to the Human rights and the constitution. Prof. Patricia Kameri-Mbote our moderator for the debate that canvassed two viewpoints; one being Sexual Harassment – A universalist Approach and the other Sexual Harassment – A cultural Relative Approach. The debate features constitutional and human rights lawyers and academics: Wachira Maina, Charles Kanjama, Dr. Agnes Meroka & Dr. Duncan Ojwang